2021
DOI: 10.1093/jas/skab243
|View full text |Cite
|
Sign up to set email alerts
|

Detecting effective starting point of genomic selection by divergent trends from best linear unbiased prediction and single-step genomic best linear unbiased prediction in pigs, beef cattle, and broilers

Abstract: Genomic selection has been adopted nationally and internationally in different livestock and plant species. However, understanding whether genomic selection has been effective or not is an essential question for both industry and academia. Once genomic evaluation started being used, estimation of breeding values with pedigree BLUP became biased because this method does not consider selection using genomic information. Hence, the effective starting point of genomic selection can be detected in two possible ways… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The selected animals with many genotyped progenies are also more likely to have MS greater than zero [34]. The larger MS has an impact on genetic trends when animals are selected based on genomic information, especially if the selection happens before phenotypes are recorded [35].…”
Section: Modelmentioning
confidence: 99%
“…The selected animals with many genotyped progenies are also more likely to have MS greater than zero [34]. The larger MS has an impact on genetic trends when animals are selected based on genomic information, especially if the selection happens before phenotypes are recorded [35].…”
Section: Modelmentioning
confidence: 99%
“…Advancements in animal breeding and the role of national breeding organizations have considerably contributed to the improvements of many traits such as growth rate, beef quality, and milk production and quality, among others. For instance, in Angus, Abdollahi-Arpanahi et al (2021a) reported annual genetic gains for weaning weight between 4.06 kg and 4.96 kg from 2006 to 2018. In US Holstein, fat yield increased by about 300 kg between 1957 and 2015, 50% of which was due to genetic progress (Cole and VanRaden 2018).…”
Section: Genetic Evaluations Of Quantitative Traitsmentioning
confidence: 99%